Benthic fluxes of metals into the Pearl River Estuary based on 224Ra/228Th disequilibrium: From alkaline earth (Ba) to redox sensitive elements (U, Mn, Fe). (15th September 2018) - Hong, Qingquan; Cai, Pinghe; Geibert, Walter; Cao, Zhimian; Stimac, Ingrid; Liu, Lingfeng; Li, Qing
Abstract: We extended the 224 Ra/ 228 Th disequilibrium approach to examine benthic fluxes of a variety of metals, ranging from alkaline earth (Ba) to redox sensitive elements (U, Mn, and Fe), into the Pearl River Estuary (PRE), China. Depth profiles of 224 Ra and 228 Th in bulk sediment, as well as dissolved 224 Ra and trace metals in porewater were measured along a transect within the estuary in July 2015. Significant deficit of 224 Ra relative to 228 Th was commonly observed in the upper 0–15 cm sediment. We took advantage of the 224 Ra/ 228 Th disequilibrium in the bottom sediments to construct a full mass balance of 224 Ra in the overlying water column. We demonstrated that porewater exchange (PEX) processes with scale lengths of several centimeters are the predominant mechanism for solute transport between sediments and overlying waters in the PRE. In contrast, deep porewater flow or submarine groundwater discharge (SGD) with scale lengths of "meters to kilometers" are a negligible component in the water column budget of 224 Ra. Strong correlations between dissolved 224 Ra and trace metals (Ba, U, Mn, and Fe) in porewater were frequently observed in the study region. This likely reflects a fact that geochemical cycling of alkaline earth elements (e.g., Ra and Ba) and redox sensitive elements (like U) in sediments was closely linked to diagenetic reactions of manganese and iron oxides. This linkage makes it possible to quantify benthic fluxes of alkaline earth and redox sensitive metals using 224 Ra/ 228 Th disequilibrium in sediments. Benthic Ba fluxes based on 224 Ra/ 228 Th disequilibrium were found to vary from virtually nil to 320 μmol m −2 d −1 within the PRE. The highest flux was identified at salinity = 3.0–7.8 and could lead to an elevation of 54 nmol Ba l −1 in the water column, which well reproduced the Ba excess frequently observed in the low salinity domain of the estuary. Benthic fluxes of redox sensitive U ranged from −0.42 ("−" denotes flux into sediment) to 1.3 μmol m −2 d −1 . This could only cause a change of −0.1 to 0.3 nmol U l −1 in the water column, which is very small when compared to the U concentration of 13–14 nmol l −1 in the northern South China Sea. We therefore predicted that water column U in the PRE must behave conservatively during mixing. This prediction is consistent with historical measurements of water column U concentration within the PRE. Large benthic fluxes of Mn and Fe were generally acquired with the 224 Ra/ 228 Th disequilibrium method. They varied from virtually nil up to 97 mmol m −2 d −1, and from zero to 27 mmol m −2 d −1, respectively. These estimates are 1–2 orders of magnitude higher than historical measurements based on the traditional incubation method in other coastal settings. Nonetheless, they are in agreement with a simple consideration of Mn and Fe mass balances in the sediment. An important implication of this study is that the role of coastal sediments in estuarine geochemistry of trace metals may need to be re-evaluated.